An aggregate import demand function for Malaysia: A cointegration and error correction analysis - Tang, Tuck Cheong; Alias, Mohammad (Universiti Utara Malaysia, 2000)
This paper examines the long run relationship between Malaysia's aggregate inports and income and relative price using Johansen cointegration analysis. Annual data for the period 1970 to 1998 were used. The estimated long run elasticities of import demand with respect to income and relative prices are 1.5 and 1.8 respectively. In the short run, growth in imports is influenced by growth in current income and relative prices. The insignificance of the lagged error correction term in the ECM implies that there is no disequilbrium in the long run relationship. AS import demand is income elastic in the long run, economic growth may have negative implications on the balance of payments. The high long run cross price elasticity suggests that domestic inflation needs to be kept in check, as domestic inflation would increase the volume of imports.